Effectiveness of the toxicant DRC‐1339 in reducing populations of common ravens in Wyoming - Luke W. Peebles; Michael R. Conover (Wildlife Society Bulletin)
ABSTRACT Common raven (Corvus corax) populations have increased several‐fold in the western United States during the past century; these birds cause problems when they kill new‐borne lambs and calves and depredate nests of greater sage‐grouse (Centrocercus urophasianus). The toxicant DRC‐1339 is used by U.S. Department of Agriculture/Animal and Plant Health Inspection Service Wildlife Services to manage common raven populations and reduce the severity of these problems, but it is difficult to determine how many ravens are killed by an application because carcasses are rarely found. We examined the effectiveness of DRC‐1339 applications for preventative control of ravens at 3 landfills and 5 nearby roosts in Wyoming, USA, from 2013 through 2015. Wildlife Services removed 23%, 34%, and 7% of the radiomarked sample of ravens in southwestern Wyoming during 2013, 2014, and 2015, respectively, according to Kaplan–Meier survival estimates. During the 3 winters, 235 of 240 raven carcasses that we collected died from DRC‐1339 poisoning. The following year, raven fecundity and immigration had offset most, but not all, of the mortality produced by the DRC‐1339 program. Raven population estimates declined 9% from the 2013 winter to the 2014 winter and 12% from the 2014 winter to the 2015 winter, based on telemetry data and roost counts. Ravens did not avoid landfills after they were treated with DRC‐1339 probably because few ravens died there. Estimated mortality rates from DRC‐1339 applications based on carcass counts underestimated the actual rates by 79% and landfill counts of ravens underestimated it by 49%. Roost count estimates of mortality were within 15% of the actual mortality rate. © 2016 The Wildlife Society.